Prostorski obrat, literarna veda in slovenska književnost - Juvan, Marko (Primerjalna književnost, 2013)
Despite its postmodern articulation, the spatial turn is productive for literary studies as a remaking of Kant's attempt to base knowledge on the scientific character of geography and anthropology, and as an improvement of historical contextualization methods through the dialectics of ontologically heterogeneous spaces. This article presents three examples of appropriating spatial thought in literary studies: the modernization of traditional literary geography in research on the relations between geospaces and fictional worlds (Piatti, Westphal), the systematic analysis of genre development and the spatial diffusion of genres using analytical cartography (Moretti), and the transnational history of literary culture spaces (Valdés, Neubauer, Domínguez, etc.). The article concludes by outlining the research project led by the author, in which GIS technologies are used to map and analyze data on the media, institutions, and actors of Slovenian literature in order to demonstrate how interaction between "spaces in literature" and "literature in spaces" has historically established a nationalized and esthetically differentiated literary field.
Keywords: prostorski obrat; humanistika; literarna veda; literary science; literarna geografija; GIS; transnacionalna komparativistika; literarni sistem; literarni prostor; Slovene literature; slovenska književnost; literarne študije